ANALISIS PENGARUH SIFAT REOLOGI TERHADAP KEHILANGAN ENERGI PADA SISTEM TRANSFER SUSU - Siti Mechram; Darwin Darwin; Ratna Ratna (AGRICOLA, 2013)
This research aimed to know the influence of rheological properties of cream to energy losses that occured during transporting process. In addition, this research was conducted by using a computer programming designed for calculating and analysing any complicated data. Those rheological properties were derived from analysis in the laboratory, such as viscosity from any kind of cream. Results analysed by a computer programming revealed that flow behaviour Index (n) and consistency coefficient (m) were the rheological properties interacting with each other since these parameters were the viscosity of cream that influences energy losses in the transport system. Once the total of energy losses was obtained from the system, the pump power required for transfering the product also can be known. Based on the simulation conducted by using rheological parameters of cream with consistency coefficient of 4.5 PaSn, and flow behaviour Index at 0.772 was obtained total energy losses at 282.76 J/kg with the pump power requirement at 0.285 kW. Once consistency coefficient was 7.16 PaSn, and flow behaviour Index was at around 0.768, the total of energy losses increased to 426.30 J/Kg with pump power requirement at 426.30 J/Kg